Pemberian Aromaterapi Geranium melalui Diffuser terhadap Penurunan Nyeri Pasien Pasca Operasi Urologi - Serin Izzatut Taqiyah; Sugiharto Sugiharto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of geranium aromatherapy via a diffuser on pain reduction in post-urological surgery patients. The method used was a case study using an evidence-based nursing approach in five post-urological surgery patients at Ir. Soekarno General Hospital, Sukoharjo. The results showed that all patients experienced a reduction in pain after receiving geranium aromatherapy. The average pain scale before the intervention was in the moderate pain category (VAS 5–6), which then decreased to mild pain (VAS 2–4) with an average reduction of 2.8 points. In conclusion, geranium aromatherapy via a diffuser is effective as a complementary therapy in helping reduce pain intensity in post-urological surgery patients. Keywords: Geranium Aromatherapy, Diffuser, Post-Operative Pain, Complementary Therapy, Urology